Tunable optical narrowband filter using a gain-coupled phase-shift-controlled distributed feedback laser - Kian Yong , Lim; Low, A.L.Y.; Su Fong , Chien; Ghafouri-Shiraz, H. (2005)
In this paper, we have proposed and analyzed a new tunable optical narrowband filter using gain-coupled phase-shift-controlled distributed feedback (GC-PSC-DFB) laser diode. Coupled-mode equations are solved by using the transfer matrix method (TMM). The GC-PSC-DFB filters offer a stable single-mode bandpass output, similar to that obtained with phase-shifted index-coupled structures. However, GC structures do not suffer from the severe longitudinal spatial hole burning (SHB) that occurs in high-coupling quarter-wave-shifted DFB filters. This SHB can cause multimoded behavior for high-input signal power. Various filter parameters such as wavelength tuning range, side-mode suppression ratio (SMSR), and channel gain deviation have been investigated and discussed. Our results show that the GC DFB structures offer a wider tuning range of 23.3 angstrom compared with the similar index-coupled DFB structures with nearly steady bandwidth of 12 GHz, while maintaining 41.8-dB constant gain.